Simultaneous control with artificial intelligence to mitigate irregularities in the Vaso de Leche Program of the Local Governments - Valladares Zúñiga, José Gabriel (2018)
This article describes how the simultaneous control with artificial intelligence in the “Vaso de leche” (glass of milk) Program will mitigate the irregularities found in the control operations after the exonerations of the selection processes, it was found that this affected the supply timing of the foods of the Program. These irregularities exist because the administrators of the municipalities are not aware that the “Vaso de leche” is the breakfast of the infants who live in extreme poverty and are not supervised in an appropriate timing management by the Bodies of the National Control System, and they see in this Program the opportunity to benefit, prior agreement with the suppliers. In view of this, this article proposes processes with artificial intelligence where Database Knowledge will host the norms´ structures related to the PVL. The facts about municipal official’s activities will be entered into the Fact Database. These data will be validated the system, showing the correct conclusion or the alerts that will be sent to them to correct and correctly conclude their activity. Thus, the functions will be fulfilled in a timely manner, and the municipality will arrive to supply itself opportunely, during all the months of the year.